Empowering Data Spaces for Future Mobility: Exploring Organisational Roles - Gessler, Jens; Rychlik, Hanspeter; Schulz, Wolfgang H. (Journal of Telecommunications and the Digital Economy, 2025)
Recognising the growing demand for sovereign and interoperable data exchange in advanced mobility services, this paper presents a conceptual framework for developing data spaces within the data economy. Drawing on the Gaia-X initiative, we address the challenges of ensuring data sovereignty and cross-organisational collaboration in complex, diverse data ecosystems. By applying the Institutional Role Model (IRM), we systematically identify and classify 32 distinct organisational roles, organised into eight overarching meta-roles, that are crucial for the successful operation of a data space. Based on expert interviews and the in-depth analysis of two practical use cases, our approach uncovers how technological and economic roles interact to enable the seamless and sovereign exchange of mobility data. The findings enhance theoretical understanding of role-based data space structures and provide insights into data ecosystems’ design, governance, and implementation. Stakeholders looking to leverage data space for efficient, sovereign, and innovative mobility services will find these insights highly valuable.